A Research on HMM based Speech Recognition in Spoken English - Wang, Na; Zhang, Xiaohong; Sharma, Ashutosh (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: The computer assisted speech recognition system enabling voice recognition for understanding the spoken words using sound digitization is extensively being used in the field of education, scientific research, industry, etc. Objective: This article unveils the technological perspective of automated speech recognition system in order to realize the spoken English speech recognition system based on MATLAB. Methods: A speech recognition technology has been designed and implemented in this work which can collect the speech signals of the spoken English learning system and then filter those speech signals. This paper mainly adopts the preprocessing module for the processing of the raw speech data collected utilizing the MATLAB commands. The method of feature extraction is based on HMM model, codebook generation and template training. Results: The research results show that the recognition accuracy of 98% is achieved by the spoken English speech recognition system studied in this paper. It can be seen that the spoken English speech recognition system based on MATLAB has high recognition accuracy and fast speed. Conclusion: This work addresses the current research issued needed to be tackled in the speech recognition field. This approach is able to provide the technical support and interface for the spoken English learning system.
Keywords: MATLAB